2018
DOI: 10.1371/journal.pone.0190706
|View full text |Cite
|
Sign up to set email alerts
|

Time series sightability modeling of animal populations

Abstract: Logistic regression models—or “sightability models”—fit to detection/non-detection data from marked individuals are often used to adjust for visibility bias in later detection-only surveys, with population abundance estimated using a modified Horvitz-Thompson (mHT) estimator. More recently, a model-based alternative for analyzing combined detection/non-detection and detection-only data was developed. This approach seemed promising, since it resulted in similar estimates as the mHT when applied to data from moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…Estimated annual survival in all 4 years using collared and uncollared calves were similar (within 95% CIs) and closely match rates estimated by Lenarz et al () in the same study area during 2002–2008, before the declining population trend was indicated by the MNDNR's annual survey (Giudice et al , ArchMiller et al , DelGiudice ). Our observed rates approach those reported in northern New Hampshire, northeastern Alberta, and western Interior Alaska (0.29–0.45; Hauge and Keith , Musante et al , Keech et al ) but were 46% lower than rates observed in Ontario (0.64; Patterson et al ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Estimated annual survival in all 4 years using collared and uncollared calves were similar (within 95% CIs) and closely match rates estimated by Lenarz et al () in the same study area during 2002–2008, before the declining population trend was indicated by the MNDNR's annual survey (Giudice et al , ArchMiller et al , DelGiudice ). Our observed rates approach those reported in northern New Hampshire, northeastern Alberta, and western Interior Alaska (0.29–0.45; Hauge and Keith , Musante et al , Keech et al ) but were 46% lower than rates observed in Ontario (0.64; Patterson et al ).…”
Section: Discussionsupporting
confidence: 83%
“…Annual adult survival, 81−88% during the same interval, was moderately depressed and less variable (Carstensen et al ). These demographic rates likely account for the poor performance, but recent stability, of this depressed population (ArchMiller et al , DelGiudice ).…”
Section: Discussionmentioning
confidence: 99%
“…Several moose populations along the southern geographic extent of their range have exhibited declines in abundance and/or compromised health (Dou, Jiang, Stott, & Piao, 2013;Grøtan, Saether, Lillegård, Solberg, & Engen, 2009;Monteith et al, 2015;Murray et al, 2006;Ruprecht et al, 2016), while others appear to be healthy (Brimeyer & Thomas, 2004;Murray et al, 2012;Wattles, Zeller, & DeStefano, 2018). In northeastern Minnesota (NEMN), which is high-quality moose habitat, moose declined 50% in abundance over the last decade (2005DelGiudice, 2016;ArchMiller, Dorazio, St. Clair, & Fieberg, 2018). A growing wolf population that has benefited from legal protection and the seasonal availability of deer is a primary driver in the decline of moose in NEMN (Barber-Meyer & Mech, 2016;Mech & Fieberg, 2014;Mech, Fieberg, & Barber-Meyer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The survey provides estimates of abundance (including 90% confidence intervals [CI]), percent calves, calf:cow and bull:cow ratios, and percent cows observed with twins. A sightability model corrects for visual obstruction and is used to adjust abundance (ArchMiller et al, ; Fieberg, ; Giudice, Fieberg, & Lenarz, ; Steinhorst & Samuel, ), but raw data, adjusted for sampling, are used to calculate other metrics using the combined ratio estimator (Cochran, ). The sightability model was based on radiocollared moose during 2004–2007 (Lenarz et al, , ); logistic regression indicated visual obstruction was the most influential covariate in moose detection, so visual obstruction (proportion obstructed by vegetation) is estimated within a ~10‐m radius around the first observed moose in a group (Giudice et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Assessing ecology and management of wildlife requires knowledge of population trends over time. Surveys can reveal trends but their effectiveness to do so depends on their precision and accuracy (ArchMiller, Dorazio, St. Clair, & Fieberg, ). Examining trend data can be used to estimate a population's demographic rates, which can otherwise be costly and invasive to obtain through tracking of a representative sample of individuals.…”
Section: Introductionmentioning
confidence: 99%